Competing Platforms and Transport Equilibrium - Rosaia, Nicola (Econometrica, 2025)
I study whether platform competition in app‐based transportation generates waste and whether consolidating competing networks would improve efficiency. I build a spatial model of a ride‐hailing market where competing platforms set prices strategically and estimate it using detailed data from two major platforms in New York City. Comparing the status quo to simulated counterfactuals, I find that: (i) platform market power and the fragmentation of users across networks cause a $176 million annual loss in social welfare and waste 21% of driver‐generated traffic; (ii) a platform merger would trade off gains from pooling all users into a single network against harms from greater market power, reducing traffic by 8% but lowering consumer surplus by $77 million per year due to a 4% price hike; and (iii) interoperability regulations would bring these gains without undermining competition, reducing wasteful traffic by 6% while raising consumer surplus by $63 million per year.